Deregulasi Di Indonesia Perkembangan Dan Dampaknya Terhadap Perbankan - Nuryasman MN; Hidayat Wiweko (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2001)
Deregulation packages are developed by the government with the aim to enhance the development of the banking system and the national economy. This deregulation has a certain impact on the development of the banking system, i.e on the number of banks and bank offices, the number of funds gathered from the society and credits given, which forms the positive side of deregulation. But on the other side, deregulation also has its negative side which should be taken into consideration to face the existing challenges and in order to be able to compete with other banks in the globalization era.